Addressing Bandwidth-Driven Flow Allocationin RINA - Michal Koutenský; Vladimír Veselý; Vincenzo Maffione (Computers, 2020)
Effective capacity allocation is essential for a network to operate properly, providing predictable quality of service guarantees and avoiding bottlenecks. Achieving capacity allocation fairness is a long-standing problem extensively researched in the frame of transport and network layer protocols such as TCP/IP. The Recursive InterNetwork Architecture offers programmable policies that enable more flexible control on the mechanics of network flow allocation. In this paper, we present our version of one of these policies, which provides flow allocation according to the bandwidth requirements of requesting applications. We implement the bandwidth-aware flow allocation policy by extending rlite, an open source RINA implementation. Our evaluation shows how the policy can prevent links from becoming oversaturated and use alternate paths to achieve high total link data-rate use.